2013
DOI: 10.3390/brainsci3031060
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Wrong Way with the Right Hemisphere

Abstract: Reading is a complex process, drawing on a variety of brain functions in order to link symbols to words and concepts. The three major brain areas linked to reading and phonological analysis include the left temporoparietal region, the left occipitotemporal region and the inferior frontal gyrus. Decreased activation of the left posterior language system in dyslexia is well documented but there is relatively limited attention given to the role of the right hemisphere. The current study investigated differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…Reduced bilateral occipitotemporal activation was also observed in a metaanalysis of children with DD [31]. Additionally, older children and adults with DD also display increased right hemispheric activity during reading and reading-related tasks compared to controls [32]. The absence of activation differences in frontal and right hemisphere regions between typically developing and children with DD may suggest that these differences, often found in adults, reflect compensatory strategies.…”
Section: The Neural Basis Of Developmental Dyslexiamentioning
confidence: 76%
“…Reduced bilateral occipitotemporal activation was also observed in a metaanalysis of children with DD [31]. Additionally, older children and adults with DD also display increased right hemispheric activity during reading and reading-related tasks compared to controls [32]. The absence of activation differences in frontal and right hemisphere regions between typically developing and children with DD may suggest that these differences, often found in adults, reflect compensatory strategies.…”
Section: The Neural Basis Of Developmental Dyslexiamentioning
confidence: 76%
“…Recently, studies utilizing functional magnetic resonance imaging, have identified a neurological movement connection to dyslexia (Waldie et al, 2013). According to Waldie and colleagues, "Our participants with dyslexia also showed over activation in the right hemisphere regions of the putamen and precentral gyrus during both regular and pseudo word lexical decision making.…”
Section: Introductionmentioning
confidence: 89%
“…In participants with language impairment, a number of studies have reported a higher incidence of atypical laterality or lower laterality indices when compared to control groups (Badcock, Bishop, Hardiman, Barry, & Watkins, 2012;Bishop, Holt, Whitehouse, & Groen, 2014;de Guibert et al, 2011;Illingworth & Bishop, 2009;Waldie, Haigh, Badzakova-Trajkov, Buckley, & Kirk, 2013;Whitehouse & Bishop, 2008). This has suggested the possibility that atypical lateralisation could constitute an endophenotype for language impairment, mediating the relationship between an original etiological factor such as a genetic predisposition and impaired language function (Bishop, 2013).…”
Section: Language Lateralisation and Language Ability/impairmentmentioning
confidence: 99%